Broadband metamaterial absorber on a single-layer ultrathin substrate. Issue 1 (2nd January 2019) - Sen, Gobinda; Kumar, Mukesh; Islam, Sk Nurul; Das, Santanu
Abstract: In this article, a broadband metamaterial microwave absorber on a low-cost FR-4 Epoxy substrate is proposed. The unit cell of the absorber consists of a staircase shape metallic patch placed on the top of the metal-backed ultrathin dielectric substrate having a thickness of 1.9 mm (0.07 λ 0 ). The absorption of more than 90% is achieved with this proposed low profile single-layer microwave absorber throughout the operation band from 8.86 to 15.5 GHz. The performance is analyzed for different values of incident angle, polarization angle, substrate height, and dielectric constant. The surface current and the power loss density at the top and bottom planes at the two absorption peaks of 9.46 and 13.90 GHz are also analyzed to elaborate the absorption mechanism of the structure. Experimental result closely follows the simulated one. The broadband characteristics of the design with relative absorption bandwidth (RAB) of 54.51% at both TE and TM polarizations of incident wave for a wide incident angles makes it versatile for applications in the X and Ku bands of microwave frequencies. The proposed work is very compact (unit cell size: 0.22 λ 0 ) with ultrathin substrate height (0.07 λ 0 ) and giving RAB performance of 54.51% comparable with that of others. Thus with this single-layer low-cost substrate material a broadband absorber is achieved.